ANALISIS STRATEGI PEMBELAJARAN SCAFFOLDING DALAM MENINGKATKAN KEMAMPUAN LITERASI PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA: STUDI LITERATUR - Misa Febriana; Salsa Bila Putri; Aizya Flora; Helty; Liza Septa Wilyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students' literacy skills in Indonesia remain a serious challenge, particularly in the Indonesian Language subject, with PISA 2022 placing Indonesia at a score of 359, well below the OECD average of 476. This systematic literature study aims to critically analyze scaffolding concepts, map prior research findings, formulate an implementation model, identify multidimensional impacts on literacy, and identify research gaps and pedagogical implications. Data were collected through searches on Google Scholar, SINTA, DOAJ, Garuda, Scopus, and ERIC using thematic keywords, yielding 112 initial sources that were then selected through a stepwise PRISMA-adapted protocol (deduplication, title-abstract screening, and full-text eligibility assessment) to 28 final sources (20 national, 8 international). Results indicate: (1) scaffolding is proven effective in enhancing reading, writing, critical, and digital literacy; (2) scaffolding effectiveness is contextual and depends on teacher TPACK competence; (3) scaffolding in the Indonesian context faces unique challenges of student ability heterogeneity and infrastructure limitations; (4) research gaps exist in long-term scaffolding studies, standardized measurement, and hybrid digital-conventional models. This study produces a novel six-stage conceptual implementation model synthesized from national and international literature, along with an optimal conditions framework and a future research agenda.